LABOR RESOURCES OF THE REGION AS A FACTOR OF ENSURING EARLY ECONOMIC GROWTH - V. Sutyagin; Y. Radyukova (Вестник Северо-Кавказского федерального университета, 2022)
Within the framework of the article, the authors made a study of the labor potential of the Tambov region and its role in ensuring long-term economic development of the region. During the analysis of population dynamics and labor resources indicators, the authors identified the key reasons for the unsatisfactory demographic situation in the region, which form a chronic shortage of labor resources. Comparative analysis with neighboring regions (as well as Moscow and the Moscow region) shows that the Tambov region currently has extremely low starting demographic and economic positions, which in the foreseeable future will not allow to reverse the trend of increasing labor deficit. As a result this makes the official forecasts of economic growth in the region unrealistic.